2011
DOI: 10.3762/bjnano.2.70
|View full text |Cite
|
Sign up to set email alerts
|

The atomic force microscope as a mechano–electrochemical pen

Abstract: SummaryWe demonstrate a method that allows the controlled writing of metallic patterns on the nanometer scale using the tip of an atomic force microscope (AFM) as a “mechano–electrochemical pen”. In contrast to previous experiments, no voltage is applied between the AFM tip and the sample surface. Instead, a passivated sample surface is activated locally due to lateral forces between the AFM tip and the sample surface. In this way, the area of tip–sample interaction is narrowly limited by the mechanical contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Writing of metallic structures with the tip of an atomic force microscope as a “nano-electrochemical pen” was performed as described in our previous work [12]. A glass substrate covered with a polycrystalline gold film is used as a substrate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Writing of metallic structures with the tip of an atomic force microscope as a “nano-electrochemical pen” was performed as described in our previous work [12]. A glass substrate covered with a polycrystalline gold film is used as a substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The results of previously reported [12] already showed that once an area or line along the surface is activated with the AFM tip, the passivation layer starts to regrow within a certain time, which was typically on the order of seconds (depending on the chemical parameters of the system such as concentrations, pH value), requiring a continuous reactivation of the active area of the surface with the tip of the AFM to allow for the nucleation of further islands. Assuming this, a repeated scanning of the same line or trace with the AFM tip is needed during the structuring process to prevent repassivation of the tip-activated areas before the deposition process is completed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feature sizes that can be achieved with this method, however, are limited and the preparation of sub-micrometer sized patterns is challenging or even impossible for µCP. The fabrication of structures within SAMs [26] of higher resolution can be obtained by nanoshaving and nanografting [27] or other methods based on scanning probe microscopy techniques, e.g., atomic force microscopy (AFM) [2829]. Both lithography methods allow for lateral structuring with resolutions down to several nanometers.…”
Section: Introductionmentioning
confidence: 99%